The Role of the Agri-Food Sector in Ensuring the Economic Security of Ukraine - Mostenska, T.L.; Mostenska, T.G.; Vienažindienė, M.; Chorna, L.; Yurii, E.; Kovtun, O. (My University, 2024)
The article examines the influence of the agri-food sector on the state of economic security of Ukraine. Definitions of economic security are given and approaches to characterizing its structure are analyzed. The analysis made it possible to determine that most authors include food security in the structure of economic security. The agri-food sector influences economic security, influencing both food security through the formation of the supply of food products in the domestic market and ensuring the formation of income of the population (creating jobs, running one’s own business), and due to the formation of gross added value in the agri-food sector. According to the indicators of 2022, almost 11% of the gross added value of Ukraine accounted for agricultural production and the production of food products, beverages and tobacco products (16.1% in 2021). The year 2022 was characterized by a significant decrease in the volume of foreign trade in products of the agro-industrial complex, and there were also changes in its structure. The full-scale war with the Russian federation caused direct and indirect losses in the agri-food sector of Ukraine, which significantly affects food and economic security. In order to determine the prospects for the development of the agricultural sector, the authors found out the risks of production in the agri-food sector.